2020
DOI: 10.21203/rs.2.21208/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discriminative Pattern of Reduced Cerebral Blood Flow in Parkinson's Disease and Parkinsonism-Plus Syndrome: an ASL-MRI study

Abstract: Background: Accurate identification of Parkinson's disease (PD) and Parkinsonism-Plus syndrome (PPS), especially in the early stage of the disease, is very important. The purpose of this study was to investigate the discriminative spatial pattern of cerebral blood flow (CBF) between patients with PD and PPS.Methods: Arterial spin labeling (ASL) perfusion-weighted imaging was performed in 20 patients with PD (mean age 56.35±7.56 years), 16 patients with PPS (mean age 59.62±6.89 years), and 17 healthy controls (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Reduced CBF has been demonstrated in patients with PDD (Cheng et al, 2020;Lin et al, 2017;Melzer et al, 2011;Wei et al, 2016) and DLB (Fong et al, 2011), and is associated with cognitive deficit (Cheng et al, 2020;Melzer et al, 2011;Paschali et al, 2009). In patients with DLB, AChEI were able to improve perfusion in the temporal, parietal and occipital cortices, and were associated with improved verbal fluency (Fong et al, 2011).…”
Section: Parkinson's Disease Dementia and Dementia With Lewy Bodiesmentioning
confidence: 99%
“…Reduced CBF has been demonstrated in patients with PDD (Cheng et al, 2020;Lin et al, 2017;Melzer et al, 2011;Wei et al, 2016) and DLB (Fong et al, 2011), and is associated with cognitive deficit (Cheng et al, 2020;Melzer et al, 2011;Paschali et al, 2009). In patients with DLB, AChEI were able to improve perfusion in the temporal, parietal and occipital cortices, and were associated with improved verbal fluency (Fong et al, 2011).…”
Section: Parkinson's Disease Dementia and Dementia With Lewy Bodiesmentioning
confidence: 99%
“…It is the central area of Broca's sports language area and participates in the evaluation of sensory and emotional information [23] . Research has shown that there is a certain connection between this area and Parkinson's syndrome [24] . Yu et al reported that the ALFF value of the left IFG was significantly reduced in patients with diabetic retinopathy [25].…”
Section: Analysis Of Low Alff Values In the De Groupmentioning
confidence: 99%